2020
DOI: 10.3417/2020479
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Reticulate Evolution of North Temperate Haplostemonous Ludwigia (Onagraceae)

Abstract: While it is known that whole genome duplication (WGD) and reticulate evolution play important roles in plant evolution, the origins and evolutionary histories of most polyploid and reticulate groups are still poorly known. The North Temperate haplostemonous (NTH) Ludwigia L. (sections Isnardia (L.) W. L. Wagner & Hoch, Ludwigia, Microcarpium Munz, and Miquelia P. H. Raven) group, characterized by having 4-merous and haplostemonous flowers, pluriseriate and free seeds, glabrous and convex nectaries, and a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 68 publications
6
20
0
Order By: Relevance
“…The conflicts between molecular and morphological data are not rare in plants (e.g., Bremer and Struwe 1992 ; Schuster et al 2018 ; Lu et al 2021 ). These conflicts might infer some convergent evolution and/or hybridization in the evolutionary history (e.g., Ran et al 2018 ; Soreng and Davis 2000 ; Liu et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The conflicts between molecular and morphological data are not rare in plants (e.g., Bremer and Struwe 1992 ; Schuster et al 2018 ; Lu et al 2021 ). These conflicts might infer some convergent evolution and/or hybridization in the evolutionary history (e.g., Ran et al 2018 ; Soreng and Davis 2000 ; Liu et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Isnardia currently contains 22 taxa, including five diploids, 11 tetraploids, four hexaploids, one octoploid, and one taxon with an unknown ploidy level (Table 1 ) (Raven 1963 ; Raven and Tai 1979 ; Peng 1988 , 1989 ; Peng et al 2005 ; Wagner et al 2007 ; Arya et al 2020 ; Liu et al 2020 ). Isnardia are wetland weeds characterized by their creeping or erect stem, 4-merous and haplostemonous flowers, terete or globose capsules, and pluriseriate and free seeds (Wagner et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ludwigia L. (Eyde 1977 , 1978 , 1981 ). Recent molecular phylogenies revealed that this complex is a monophyletic group with strong (Liu et al 2020 ) or weak (Liu et al 2017 ) support, and sect. Ludwigia is sister to the complex (Liu et al 2017 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations